Genes of cancer-related fatigue: a scoping review - Song, Yuqing; Sun, Xuefeng; Shen, Lu; Qu, Zihan; Yin, Jiawei; Wang, Zilin; Zhang, Hongshi (Frontiers in Oncology, 2024)
BackgroundCancer-related fatigue (CRF) is a prevalent adverse effect experienced by cancer patients while receiving and after treatment, impacting as many as 90% of individuals. Although CRF is common, the genetic processes responsible for it and their influence on individual vulnerability are not well understood and are still being investigated.ObjectiveThe primary objective of this scoping review is to identify and assess genes linked to the vulnerability and severity of CRF. This will help us better understand the genetic factors involved and assist in developing targeted nursing treatments in clinical settings.MethodsThis review followed the PRISMA guidelines. A comprehensive search was performed in databases, such as PubMed, EMBASE, Web of Science, Cochrane Library, SinoMed, CNKI, and VIP, encompassing genetic association studies on CRF published up to February 25, 2024. The JBI Critical Appraisal Tools were used to assess the quality of observational studies.ResultsThis evaluation encompassed a comprehensive analysis of 14 studies that involved 3,254 patients. The results indicate strong connections between CRF and various inflammatory cytokines (IL-4, IL-6, IL-8, IL-10, IL-1β), tumor necrosis factor-alpha (TNF-α), catechol-O-methyltransferase (COMT), and circadian rhythm genes (CLOCK, PER).ConclusionThis scoping review emphasizes the significant genetic factor in CRF, with multiple genes showing distinct effects on cancer fatigue symptoms. Identifying these genes enhances our comprehension of CRF and unveils novel avenues for cancer treatment approaches. Future research should prioritize conducting cohort studies to monitor alterations in gene expression pre- and post-treatment, hence improving individualized medicinal strategies in oncology.